Effect of smoking on folic acid and vitamin B12 after nonsurgical periodontal intervention - Ebru Olgun Erdemir (Blackwell Synergy, 2007)
Aim: The main purpose of this study was to investigate the effect of smoking on the serum levels of folic acid and vitamin B12 in smokers and nonsmokers with chronic periodontal disease after nonsurgical intervention. Material and Methods: The study base consisted of 45 current smokers and 43 nonsmokers. The clinical parameters included plaque index (PI), gingival index (GI), pocket depth (PD), and clinical attachment level (CAL). Folic acid and vitamin B12 were determined from peripheral blood samples. Clinical measurements and blood samples were collected at baseline and 1, 3, and 6 months after the intervention. Results: Mean PI was significantly greater in smokers compared with non-smokers throughout the observation period (po0.001). During the first month, GI levels significantly decreased in both groups. From months 1 through 6, a significant return towards an increased GI level was observed in smokers (po0.001). PD and CAL levels significantly decreased during the first month in both groups. Thereafter, increasing levels of PD and CAL were seen in both groups, although significantly more pronounced in smokers. Throughout the observation period, the mean CAL was significantly greater in smokers relative to nonsmokers (po0.001). In smokers, the mean folic acid level gradually and significantly decreased and a slight and significant decrease in mean vitamin B12 levels was observed in both groups over the entire observation period (po0.001). Conclusion: The clinical response to nonsurgical intervention is impaired by smoking and smoking seems to negatively influence the serum level of folic acid following non-surgical intervention.